Including visual criteria into predictive simulation of acrobatics to enhance the realism of optimal techniques - Charbonneau, E.; Romeas, T.; Ross, A.; Begon, M. (Sports Biomechanics, 2026)
Although trampolinists rely heavily on visual cues, visual criteria have not been introduced into predictive simulations yet. We aimed to introduce visual criteria into predictive simulations of the backward somersault with a twist and the double backward somersault in pike position including 1½ twists in the first somersault and ½ twist in the second somersault to generate innovative and safe optimal acrobatic techniques. A gradient of different weightings, ranging from none to large visual weights, was tested to find a good compromise between visual vs kinematics objectives. Four international coaches and two international judges assessed animations of the optimal techniques and of an elite athlete`s technique, providing insights into the acceptability of the optimal techniques. For the most complex acrobatics, coaches found all optimal techniques more efficient for aerial twist creation. However, they perceived them as less safe, less realistic, similarly aesthetic, and similarly appropriate for visual information intake compared with the athlete`s technique. Judges assigned fewer deductions to the simulated techniques than to the athlete`s performance. The optimal techniques with visual criteria were more similar to the athlete`s technique, highlighting the importance of including visual criteria into the optimisation of acrobatics to create innovative techniques that athletes will be able to use.